Remember, Avert, Prevent: Franz Ludwig Berthold Kihn - A Typology of "Euthanasia" - Braun, B.; Frewer, Andreas; Kornhuber, Johannes (Fortschritte der Neurologie - Psychiatrie, 2015)
The current debate on assisted suicide provides the occasion for calling to mind the role of Berthold Kihn as a psychiatrist under National Socialism. With a historical presentation of a typology of euthanasia, the Academic Psychiatry of Erlangen together with the Medical Ethics would like to sensitize discussions on assisted suicide by drawing attention to the start and end of Kihn's scientific career.Relevant archive material, primary and secondary literature were analyzed and evaluated.As Assistant and Senior Physician at the Psychiatric and Neurological Hospital of the University of Erlangen, Kihn lectured on "the elimination of the inferiors". As Director of the Psychiatric and Neurological Hospital of Jena University, Kihn selected psychiatric patients to be murdered under the "T4 action". Kihn participated in drafting a "Euthanasia Law". Despite his involvement in the murder of mentally ill, Kihn returned to Erlangen as a "Soviet Zone refugee", where a Denazification Court considered him a "hanger-on". Kihn was reintegrated in the academic faculty of the Friedrich-Alexander-University and headed a private clinic. On 21.01.1963, the State's Attorney Nuremberg-Fuerth dropped the criminal procedure against Kihn–officially due to a lack of proof of punishable guilt.An appropriate medical historical contextualization can represent an important condition for an adequate medical ethical debate on physician-assisted suicide and the involvement of psychiatrists. FINAL COMMENT: The analysis of Kihn's patterns of thought and argumentation can help sensitize those involved in debates on physician-assisted suicide and highlights the critical role of psychiatry as a discipline in this context.
EVALuna2:5663